THE LIABILITY OF THE CARRIER FOR PASSENGERS ACCIDENT - Santoso, Tulus Budi; Fitriyanti, Fadia (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2019)
Indonesia is an archipelago consisting of 17,504 islands included in the territory.Indonesia needs transportation, especially sea transportation. Sea transportationneeded to facilitate the transportation of people and goods, shipping safety.Therefore, the law which refers to the existence of improvement efforts for seatransport services, those passengers is entitled to compensation which shall beprovided by the carrier due to negligence during the transport operation. The legal basis based on Law No. 17 of 2008 on shipping, consumer protection and security of shipping to have fulfillment the rights of victims on maritime transportation. The research will open the view on the settlement on liability of carrier against the loss of passengers. The purpose for bringing a change in the practice of marine transportation when accidents happen, getting the rights of accident victims,Â providing compensation for heirs, providing compensation for the property and provide accountability for victims. The method research used is the normative method. Thisâ€™s by recovering bibiliographic data and scientific journals as well as documents relating to the problems analyzed to implementation of legal protection for passenger safety. The result of the research is to involve in sea transportation must be careful in carrying out the transportation business.